Evaluating The Impact And Legal Framework Of The Cabotage Principle In Coastal State Shipping - Abdullah, Kamarulnizam; Rachmawati, Irma; Septianita, Hesti (International Journal of Latin Notary, 2024)
The Cabotage Principle grants coastal states the authority to exclusively regulate domestic shipping within their waters. This principle allows coastal nations to prohibit foreign vessels from navigating and trading along their coastlines without permission and for clear, justified reasons. In Indonesia, foreign vessels are restricted from entering its waters unless expressly authorized. The study aims to evaluate the impact on indigenous and foreign coastal shipping firms and explore how the policy can be leveraged to enhance business opportunities for local ship operators in the coastal shipping sector. Data was collected on the charter fees for numerous regional and foreign cabotage vessels for each year within the scope of this study, assuming comparable charter rates for ships from both groups. The resulting model proposes a legal framework for the cabotage principle that involves key stakeholders, including ports, local governments, legislatures, and academic institutions. The specific goal of this research is to inform policy-making, regional studies, and international law.